2019
DOI: 10.3126/jnarc.v5i1.18674
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soil Conditioner on Carrot Growth and Soil Fertility Status

Abstract: A field experiment was conducted in popular carrot cultivar Nepa Dream using randomized complete block design (RCBD) with four replications for evaluating the effects of ten different treatments of soil conditioner in combination with organic and inorganic fertilizers on root growth and soil productivity. Soil samples from each microplot were also analyzed for soil texture, pH, organic matter, total nitrogen, available nitrogen, total phosphorus and total potassium before sowing and after harvest. Effects on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Also, the FYM results in the greater average mean diameter of soil aggregates and the higher percentage of macro-aggregates, and the mean weight diameter was assumed considered to be increased with the increase in soil organic carbon concentration (Su et al, 2006). Ayer et al, (2019) also reported that the application of FYM along with conditioner and RDF increase the root yield significantly. FYM may increase the growth and root development and improve the overall physical, chemical, and biological properties which help better nutrient absorption and utilization by plants resulting in better plant growth (Kanaujia, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Also, the FYM results in the greater average mean diameter of soil aggregates and the higher percentage of macro-aggregates, and the mean weight diameter was assumed considered to be increased with the increase in soil organic carbon concentration (Su et al, 2006). Ayer et al, (2019) also reported that the application of FYM along with conditioner and RDF increase the root yield significantly. FYM may increase the growth and root development and improve the overall physical, chemical, and biological properties which help better nutrient absorption and utilization by plants resulting in better plant growth (Kanaujia, 2013).…”
Section: Resultsmentioning
confidence: 99%